INVESTIGATION OF CONSTRUCTIONAL CHARACTERISTICS OF CUTS ON MANDREL AT PRODUCTION OF HOLLOW SLUGS OF NON-FERROUS ALLOYS - O. N. Horoshilov; O. I. Ponomarenko (Литьë и металлургия)
The calculation methods of the contact square between slug and mandrel with cuts and mandrel construction with cuts are given.